EVALUASI PENYELENGGARAAN PROGRAM PENDIDIKAN KECAKAPAN HIDUP DALAM BIDANG PENDIDIKAN LUAR SEKOLAH - Muhammad Hasbi (JIV-Jurnal Ilmiah Visi, 2006)
The study is aimed at describing the implementation of Life Skills Education Program, especiallyrelated to: (1) the level of the society’s need and the environment support to the program; (2) thecharacteristic of the learners, facilators’, organizers, learning program, learning materials, and theavailability of the facilities; (3) the implementation of the program, especially related to the activitiesof die learners, facilitators’ and organizers; (4) the program output, especially related to: the lifeskills gained by the learners and the benefits of the program for the organizers and CommunityLearning Centres (CLC).The result of descriptive analysis showed the following facts. : First, the level of society’s need forLife Skills Education Program was fairly high. Second, the environment support to the program wasfairly sufficient. Third, the characteristics of learners fulfilled the criteria, while the facilitator’sunderstanding of life skills concept was low and the ratio of facilitators and learner was not sufficient.Moreover, organizers understanding of life skills concept was low, and there were organizers who didnot have a clear organization scheme and the delivery of responsibility. Fourth, the learning programwas not integrative organized; Fifth, the quality and quantity of primary arid secondary learningmaterial were poor. Sixth, individual learning activities as well as the cross-sector coordination arestill poor. Seventh, the supervision of the program implementation was low. Eighth, the learningassessments did not use various techniques, not documented and analyzed well. Ninth, the learner’sachievement of social and vocational skills was fairly good, while their achievement of personal anddaily living skills was poor. However, to some extent, the Life Skills Education Program has givenbenefits to the organizers and Regional RTIU of CLC in South Sulawesi ProvinceKey words: life skills, nonformal education, PBKH program, learning center